PENGARUH KOMPETENSI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP KINERJA KARYAWAN - Nanik Yuzalmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Performance is the result of work that can be achieved by a person or group of people in a company in accordance with the authority and responsibility of each in an effort to achieve organizational goals illegally, does not violate the law and does not conflict with morals and ethics. Therefore, all entities must know the factors that affect employee performance. This study uses qualitative and quantitative research methods, with a population of all employees of PT Surya Dermato Medica Pekanbaru. The sampling technique in this study used the census or saturated sampling method and samples taken during 2022 were 53 employees of PT Surya Dermato Medica Pekanbaru. This study uses the SPSS version 21 program to obtain research results. The results of the study show that competence has a significant influence on employee performance. This explains that when employees have high competence, they tend to be comfortable and fast in carrying out their work because they can carry out the work they will do well according to their abilities. If employees are active at work and complete their work on time, the company's performance will increase because employees become more productive. Simultaneously Competence and OCB have an influence on employee performance. This explains that OCB will make employees more disciplined at work, besides that employees are encouraged to develop their skills and knowledge from their competencies in order to gain high trust from the company. The development of employee skills and knowledge will then have a positive impact and will improve employee performance. Based on Competency and OCB research, it can explain the factors that influence employee performance by 69.6%.